The given function is f(x) = x^2 - 5.

We can find the value of this function for different values of x by substituting them in the expression for f(x).

Substituting x = 0.5 in f(x) = x^2 - 5

=> 0.5^2 - 5

=> 0.25 - 5

=> - 4.75

**Therefore f(0.5) = -4.75**

Substituting x = h+1 in f(x) = x^2 - 5

=> (h+1)^2 - 5

=> h^2 + 2h + 1 - 5

=> h^2 + 2h - 4

**Therefore f(h+1) = h^2 + 2h - 4**

To find the value of the function g(x) = x^2 - 5 for x=0.5 and x=h+1.

(1)To find the value of g(x) = x^2-5, for x = 0.5, we substitute 0.5 in place of x in x^5-5 and then calculate the value.

Therefore g(0.5) = 0.5^2-5 = 0.5*0.5-5

g(0.5) = 0.25-5

g(0.25) = -4.75.

(ii) To find g(x) for x= h+1 we put h+1 iplace of x ing(x) x^2-5:

g(h+1) = (h+1)^2-5.

g(h+1) = h^2+2h+1-5

g(h+1) = h^2+2h-4.

Therefore g(h+1) = h^2+2h-4.